Modern Art, National Culture, and Hispanophilia in Revista de Avance - Iliana Cepero (Latin American Research Review)
This article explores how the editors and contributors of Revista de Avance formulated an idiosyncratic version of visual modern art and how that discernment shaped their idea of a nationalist and regional culture. Their artistic disquisitions were influenced by complicated political agendas and funding. After the collapse of the Cuban economy in the early 1920s, the magazine’s editors, who held socialist and anti-American imperialist beliefs, looked to Spain as a cultural model. In its pages, the magazine privileged Spanish civilization and conflated it with both European modernist culture and Cuban art and literature. At the same time, Revista de Avance voiced the ideas of the Institución Hispano-Cubana de Cultura, led by Fernando Ortiz.